Spectrum Analysis of GMA Welter in Various Working Modes - (:unkn) unknown (BUDAPEST TECH, 2012)
In this study, a current drawn by a welter at initial, stable-state and finish modes is examined using spectral analysis. The current shunt measurement method is utilized in order to measure the current drawn by the welter. The study involves the examination of welding stages of a material with the electrode of a welter. First, the current drawn by the welter is measured in the initial mode of the welding process. Then the current value during the stable-state mode of the welding process is measured. Finally, the current drawn at the finishing mode of the welding process is measured. Fast Fourier Transform (FFT) of all these measured current values are calculated and spectral analysis is performed using these transforms. During the study, it is observed that current drawn by the welter during these three modes of welding are different from each other. For each mode, frequency domain analysis of the measured current is performed.
Keywords: Welters; high frequency inverter; working modes; current shunt measurement; spectral analysis; ARC WELDING MACHINE; ALUMINUM-ALLOYS